PERENCANAAN STRUKTUR BETON BERTULANG TAHAN GEMPA GEDUNG HOTEL SOLUNA 4 LANTAI DI JALAN PARIT H. HUSIN II KOTA PONTIANAK: PERENCANAAN STRUKTUR BETON BERTULANG TAHAN GEMPA GEDUNG HOTEL SOLUNA 4 LANTAI DI JALAN PARIT H. HUSIN II KOTA PONTIANAK - Islamiawan, fajlur; rasiwan, rasiwan; Ariansyah, Rona (RETENSI, 2023)
Dominated by trade and services, there will be many entrepreneur from local and abroad so that infrastructuresuch as hotels is suitable to use as a place to stay or as a meeting room for entrepreneur. Along with the times,building planning must also meet earthquake-resistant requirements and hence SNI 03-1726-2002 concerningEarthquake Resistance Planning Standards for Building Structures was made. Earthquake Resistant 4-StoreySoluna Hotel Building on Parit H. Husin II street, Pontianak City with a height of 22.5 meters from the ground,reinforced concrete structure. The Medium Moment Bearing Frame System (SRPMM) is used in the calculationof this building because the results of the Standard Penetration Test show that the building is erected on a soilwith soft conditions (site class SE) and is included in the Seismic Design category (KDS) C. In this method, theDouble System Method is used as the main structural system combined with shear walls. Earthquake loadplanning uses the 2017 Indonesian Earthquake Map by utilizing the response spectrum method in accordancewith the Indonesian National Standard (SNI) 1726-2019. The load calculation method used follows the IndonesianNational Standard (SNI) 1727-2020 and the Planning and Loading Guidelines for Building Houses (PPPURG)1987, the need for structural concrete in building construction must meet the standards set out in SNI 2847-2019.The calculation results obtained the size of 1 type of plate 12 cm; 2 types of beams 37.5/55 cm, 30/40 cm; 1 typeof column 55/55 cm; staircase and balcony plates 12 cm, 3 types of foundations P3 250 x 250 x 70 cm - pile 9D30cm; P2 250 x 170 x 70 cm - pile 6D30 cm; P1 170 x 170 x 50 cm - pile 4D30 cm.Keywords: Reinforced concrete structure, Hotel, Earthquake resistant, Spectrum response, Dual system